Functional Evaluations in the Monitoring of the River Ecosystem Processes: The Adige River as a Case Stu - M.G. Braioni; G. Salmoiraghi; F. Bracco; M. Villani; A. Braioni; L. Girelli (The Scientific World Journal)
A model of analysis and environmental evaluation was applied to 11 stretches of the Adige River, where an innovative procedure was carried out to interpret ecological results. Within each stretch, the most suitable methods were used to assess the quality and processes of flood plains, banks, water column, bed, and interstitial environment. Indices were applied to evaluate the wild state and ecological quality of the banks (wild state index, buffer strip index) and the landscape quality of wide areas of the fluvial corridor (environmental landscape index). The biotic components (i.e., macrozoobenthos, phytoplankton and zooplankton, interstitial hyporheic fauna, vegetation in the riparian areas) were analysed by both quantitative and functional methods (as productivity, litter – processing and colonisation). The results achieved were then translated into five classes of functional evaluation. These qualitative assessments have thus preserved a high level of precision and sensitivity in quantifying both the quality of the environmental conditions and the integrity of the ecosystem processes. Read together with urban planning data, they indicate what actions are needed to restore and rehabilitate the Adige River corridor.